A methodology to predict thermomechanical cracking of railway wheel treads: From experiments to numerical predictions. (December 2017) - Esmaeili, Ali; Walia, Mandeep Singh; Handa, Kazuyuki; Ikeuchi, Katsuyoshi; Ekh, Magnus; Vernersson, Tore; Ahlström, Johan
Highlights: Full-scale tests featuring three series of repeated stop braking cases is performed. Test conditions have been simulated numerically using FE analysis for ER7 material. Plasticity material model is calibrated against LCF tests at temperatures 20–625 °C. Fatigue criterion for RCF life prediction are investigated. Abstract: In the present study, thermomechanical cracking of railway wheel treads is studied by full-scale brake rig tests and finite element simulations. The main goal of the paper is to perform thermomechanical rolling contact fatigue life predictions. The wheel tread material is subjected to simultaneous mechanical and thermal loads due to rolling contact and stop braking, respectively. Full-scale tests featuring three series of repeated stop braking cases have been performed in a brake rig featuring a tread braked wheel that is in rolling contact with a so-called rail-wheel. The brake rig test conditions have been simulated numerically using the finite element method where the effect of "hot bands" on the tread is accounted for as indicated by the experimental findings. Stresses induced by temperature from braking as well as tractive rolling contact loading on the tread are considered. The mechanical response of the wheel material ER7 is obtained from a plastic Chaboche material model calibrated against data from cyclic experiments at room temperature and up to 625 °C. Finally, a strategy for prediction of fatigue life with respect to ratchetting failure is discussed.